Effects of insulin resistance on cardiovascular risk factors in obese and non-obese patients - Arıcan Tarım, Bahar; Papila Topal, Nurdan; Keskin, Özcan; Faikoglu, Gokhan; Saygısever-faikoğlu, Kübra; Uskur, Tuğçe (The European Research Journal, 2024)
Objectives: It is known that insulin resistance increases cardiovardiovascular risk. But it could not obviously be understood whether insulin resistance itself or the metabolic syndrome parameters, like obesity, that already exist in most of them, are responsible for this increased risk. Our aim is to determine cardiovascular risks in obese and non-obese insulin-resistant patients. Methods: One hundred thirty-nine patients were included in the study. They were divided into 4 groups: Group 1 (having obesity and insulin resistance), Group 2 (having only insulin resistance but not obesity), Group 3 (having obesity but not insulin resistance), and Group 4 (having neither obesity nor insulin resistance). Patients having any systemic disease were excluded. Insulin resistance is calculated via Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) formula. Electrocardiographic, echocardiographic and lipid parameters of these patients were compared. Results: High-density lipoprotein (HDL) levels of Group-4 were higher than Group 1 and Group 2. There was no statistical difference in HDL cholesterol levels between Group 3 and the others. Triglyceride and very low-density lipoprotein levels were higher in Group 1. There was no difference in P wave dispersion between the groups. In echocardigraphy, epicardial fat tissue thickness of Group 1 was significantly higher. Prevalance of diastolic dysfunction was higher in Group 1 compared to Group 4. Conclusions: Insulin resistance itself is a risk factor for low HDL levels independent of obesity. When obesity is added to insulin resistance, other cardiovascular risk factors appear, like high triglyceride levels, increase in epicardial fat tissue thickness and presence of diastolic dysfunction. Early detection of insulin resistance may alert us to the risks of cardiovascular diseases.